Estudo sobre a ocorrência de fraturas de chapas metálicas no processo de conformação incremental com o emprego de análises numéricas por elementos finitos. - Santos, Paulo Henrique Silva (Universidade Federal de São Carlos, 2025)
The mechanical forming of thin metal sheets is a growing technology that is well suited to meeting the industry's need for parts with complex geometries and low manufacturing costs. To manufacture such parts, a number of processes are being studied and developed, such as machining, die and punch forming, and incremental forming. In incremental forming with thin sheets, the process is characterized by the movement of a tool with a spherical or semi-spherical tip with a trajectory programmed by CNC logic in order to follow a predetermined path on the surface of a sheet with the imposition of incremental plastic deformations until the programmed profile is formed. The purpose of the incremental process is to enable the manufacture of parts with a wide variety of geometries and profiles without the use of dies and punches, which reduces costs and promotes the rapid manufacture of prototype parts. Stresses and deformations are adjusted based on machine parameters such as feed speed, tool rotation, lubrication, and cooling, for example. This study investigated the influence of the tool rotation speed parameter on the incremental stamping (EI) process based on the forming limit curve (FLC) diagrams using the criteria of deformation trajectory and final deformation state, in addition to analyzing thicknesses, stamping depth, and triaxiality of stresses. For the analyses, numerical experiments were performed in the ABAQUS® program using the finite element method with the properties of the physical experiment available in the article by Magalhães, D., et al., (2025), in addition to being implemented with and without the ductile damage model. The material implemented was an aluminum sheet with a geometry of 55 x 55 x 1 mm of the AA1050/AA7050 aluminum multilayer hybrid material produced by accumulated rolling. The results showed that tool rotation had little influence on the criteria evaluated, as did friction and density in the cases tested, but differences were found in the results with and without the ductile damage model. In addition, the results showed that the triaxiality of stresses is not constant over time and that there is a triaxiality gradient when analyzing at a single point in time.
Study on the occurrence of sheet metal fractures in the incremental forming process using finite element numerical analysis.
Keywords: Conformação incremental; Conformação; Elementos finitos; Critério de dano dúctil; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO; 9. Indústria, Inovação e Infraestrutura